A Tripartite Dilemma: Turkey, Armenia, and Azerbaijan Relations at the Intersection of Identity and National Interest - ÖZDEMİRKIRAN EMBEL, MERVE (Routledge, London/New York, 2023)
With a range of case studies from every continent, the contributors to this book analyze the challenges that arise for states living with much larger neighbors, and the policies they develop to account for this asymmetry. Bringing together the perspectives of bilateral relations and the study of small states, this book analyzes a range of scenarios where one or more smaller countries must manage relations with a much larger neighbor or neighbors, from the perspective of the smaller countries. Each case presents different priorities, depending on the relationship between the states concerned, while highlighting the commonalities across the various scenarios. The range of cases and contributors is wide and diverse, with examples including Togo’s relationship with Ghana, Mongolia’s with China, and Colombia’s with Brazil – as well as more widely known examples such as Canada and the United States, or Australia and New Zealand. A valuable resource for scholars and students of international relations, and public policy of small- and medium-sized states.
Keywords: Sosyal ve Beşeri Bilimler; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Political Science; International Relations; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; ULUSLARARASI İLİŞKİLER; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; INTERNATIONAL RELATIONS; POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; Social Sciences & Humanities